The geographical distribution of underweight children in Africa - Maarten Nubé; Benjamin G.J.S. Sonneveld (The World Health Organization, 2005)
OBJECTIVE: To study geographical patterns of underweight children in Africa by combining information on prevalence with headcounts at a subnational level. METHODS: We used large-scale, nationally representative nutrition surveys, in particular the Demographic and Health Surveys and the Multiple Indicator Cluster Surveys, which have been designed, analysed and presented according to largely similar protocols, and which report at the national and subnational levels. FINDINGS: We found distinct geographical patterns in the occurrence of underweight children, which could be linked to factors such as agronomic and climatic conditions, population density and economic integration. CONCLUSION: Patterns of underweight children cross national borders suggesting that regional characteristics and interactions need to be considered when addressing malnutrition.